MON-097 Continuous Glucose Monitoring in Youth with Type 1 Diabetes; Parental Anxiety and Parent Defined Outcomes: Results of Follow up Surveys - Alkhaled, Lina (J Endocr Soc, 2020)
Continuous glucose monitors (CGMs) can be helpful in management of type 1 diabetes (T1D). Our objectives were to explore parental reason for adding CGM to their child’s T1D management and to describe potential barriers to starting CGM. Prior to CGM initiation, the primary caregiver of a child with T1D completed validated questionnaires including Fear of Hypoglycemia Scale (FOH), State-Trait Anxiety Inventory (STAI), Problem Areas in Diabetes Scale (PAID), and an investigator developed questionnaire assessing primary reason for starting CGM. Surveys were repeated 3-8 months after adding CGM. The results of the initial surveys reported elsewhere suggest that the most common reason for starting CGM is to improve glycemic control. Out of 32 participants who completed initial surveys and intended to start CGM on their child, only 43% (N=14) started using CGM during the 3-8 month follow up period. Reasons for not starting CGM included: not having the chance to start the process of having it approved by insurance in 64% (N=9), and difficulties getting insurance to approve CGM in 28% (N=4). One participant reported that despite insurance coverage, out of pocket expense was too much. Wilcoxon Rank Sum tests were used to compare demographic variables between those that started and those that did not start CGM. Medians were used to report the results. There were no statistically significant differences between children who did and did not start CGM in terms of age (9.3 vs. 11.4 yrs, P=0.3), baseline HbA1c (8.1% vs. 9.4%, P=0.1), and diabetes duration (3.0 vs. 4.3 yrs, P=0.6). In summary, despite parental interest in CGM initiation for their children with type 1 diabetes, there remains a significant barrier to implementation from delays in getting insurance approval. Revision of policies related to CGM coverage in youth need to be revised and systems in place to expedite approval.